A third new Cyrtodactylus (Squamata: Gekkonidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam - Phung, Trung My; Schingen, Mona Van; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2014)
We describe the third new species of the genus Cyrtodactylus from Ba Den Mountain, Tay Ninh Province, southern Vietnam based on a type series consisting of eleven specimens. Cyrtodactylus thuongae sp. nov. is distinguished from the remaining Indochinese Bent-toed Geckos by a combination of the following morphological characters: size medium, with a maximum SVL of 77.6 mm; dorsal pattern consisting of blotches between limbs and on occiput and a sometimes medially opened nuchal loop; dorsal tubercles in 16–18 irregular rows; ventrals in 29–44 longitudinal rows at midbody; lateral skin folds present, lacking tubercles; femoral pore series separated from precloacal pore series in males, 0–3 on each side; precloacal pores in males absent or only one; enlarged femoral scales and precloacal scales present, separated by a series of 15–16 smaller scales; postcloacal spurs two or three; subcaudal scales slightly enlarged. This is the 32nd described Cyrtodactylus species from Vietnam.